Due diligence obligations of conduct: developing a responsibility regime for PMSCs - White, Nigel D. (Routledge, 2012)
As non-state actors, PMSCs are not embraced by traditional state-dominated doctrines of international law. However, international law has itself failed to keep pace with the evolution of states and state-based actors, to which strong Westphalian notions of sovereignty are no longer applicable. It is argued that these structural inadequacies stand in the way of international regulation of PMSCs, rather than defects in international human rights and humanitarian law per se. By analyzing understandings of legal responsibility, where such structural issues come to the fore, it is argued that, rather than attempting to resolve the essentially ideological dispute about the inherent functions of a state, regulatory regimes should focus on the positive obligations of states and PMSCs, and the interactions between them. Applying the results of this analysis, current and proposed regulatory regimes are evaluated and their shortcomings revealed.